2022
DOI: 10.1097/fm9.0000000000000141
|View full text |Cite
|
Sign up to set email alerts
|

Computerized Analysis of Antepartum Cardiotocography: A Review

Abstract: Cardiotocography measures the human fetal heart rate and uterine activity using ultrasound. While it has been a mainstay in antepartum care since the 1960s, cardiotocograms consist of complex signals that have proven difficult for clinicians to interpret accurately and as such clinical inference is often difficult and unreliable. Previous attempts at codifying approaches to analyzing the features within these signals have failed to demonstrate reliability or gain sufficient traction. Since the early 1990s, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(37 citation statements)
references
References 86 publications
0
19
0
Order By: Relevance
“…Dawes et al highlighted the advantages of such a computerized analysis 19 . In 2022, Jones et al published a review of computerized CTG with a focus on the Dawes‐Redman system 20 . Then, in the following decades, other computerized systems based on similar methodologies have been built 8,21–23 to be used during labor.…”
Section: Computerized Ctg Analysis During Labormentioning
confidence: 99%
See 1 more Smart Citation
“…Dawes et al highlighted the advantages of such a computerized analysis 19 . In 2022, Jones et al published a review of computerized CTG with a focus on the Dawes‐Redman system 20 . Then, in the following decades, other computerized systems based on similar methodologies have been built 8,21–23 to be used during labor.…”
Section: Computerized Ctg Analysis During Labormentioning
confidence: 99%
“… 19 In 2022, Jones et al published a review of computerized CTG with a focus on the Dawes‐Redman system. 20 Then, in the following decades, other computerized systems based on similar methodologies have been built 8 , 21 , 22 , 23 to be used during labor. The Omniview‐SisPorto system (Speculum S.A., Portugal) developed by Ayres‐de‐Campos et al consists of a quantitative adaptation of the FIGO's guidelines.…”
Section: Computerized Ctg Analysis During Labormentioning
confidence: 99%
“…Computer‐aided analysis of the antenatal cardiotocography (CTG) was developed by the group of Dawes and Redman from Oxford in the 1980s. Criteria for normality were developed, and a detailed description of these has been published 4,5 . An antenatal CTG trace is deemed to be normal if the Dawes–Redman criteria for normality are met 6 .…”
Section: Introductionmentioning
confidence: 99%
“…published. 4,5 An antenatal CTG trace is deemed to be normal if the Dawes-Redman criteria for normality are met. 6 When the criteria of normality are not met, a review with an experienced clinician is suggested.…”
mentioning
confidence: 99%
“…[3][4][5] These CTG patterns, however, are difficult for human visual interpretation to reliably and consistently identify. 1,6,7 It is well-established that subjective assessment of the CTG patterns suffers from poor inter-observer and intra-observer reproducibility 1,[8][9][10][11][12][13] and is associated with increased operative vaginal delivery and caesarean section rates without improving perinatal outcomes. 14,15 Computerised cardiotocography (cCTG) has been considered to be superior to conventional CTG because this approach provides more reliable and consistent interpretation of the CTG tracing.…”
Section: Introductionmentioning
confidence: 99%